A study on innovative reverse logistics and its impact of customer satisfaction - MS. B. NEERAJA; MR. NISHANTH. S (The journal of contemporary issues in business and government, 2020)
Companies are also looking for new ways to enhance their operation, customer loyalty and remain ahead of the game with their rivals in the dynamic world of production. For the past decade or so, reverse logistics has been considered a method to bring these items to life.This thesis paper aims to shed some light on the fundamentals of reverse logistics and how a management approach can be used for reverse logistics. This paper highlights the basics of reverse logistics and discusses what kind of decisions today's logistics managers have to take to develop their logistics model on a daily basis.A increasing concern to control rising global emissions has been emerging, this paper also highlights some of the impact on the environment of reverse logistics decisions and vice versa. In the theoretical history portion, the study begins by collecting the work of scholars and logistics experts in the field of logistics.A small picture of the degree to which reverse logistics has entered the manufacturing world has been drawn through a study conducted in a few manufacturing firms in India.